Chemical structure, water absorbency and thermal properties of poly(acrylamide-co-acrylic acid)-grafed-poly(styrene-co-methyl methacrylate) "raspberry" – shape like structure microgels - Ros Azlinawati, Ramli; Shahrir, Hashim; Laftah, Waham Ashaier (IOP Publishing, 2018)
This contribution presents the characterization of poly(acrylamide-co-acrylic acid)-grafted-poly(styrene-co-methyl methacrylate) [poly(AAm-co-AAc)-g-poly(St-co-MMA)] The chemical structure of poly(AAm-co-AAc)-g-poly(St-co-MMA) microgels was proposed. The effect of MBA contents on the degree of cross-linking (%), water absorbency (EWC, %), glass transition temperature, Tg and thermal degradation were studied. The degree of cross-linking (%) and EWC, % increased at 1.5 to 1.675 wt.% of MBA might be due to mono cross-links of MBA. The fluctuation of Tg and melting temperature (Tm ) from 1.85 to 2.2 wt.% of MBA might be due to di, poly and cyclic cross-links of MBA. Decomposition of poly(AAm-co-AAc)-g-poly(St-co-MMA) was slightly affected by increasing in MBA contents from 1.5 to 2.2 wt.%. Tg of poly(AAm-co-AAc)-g-poly(St-co-MMA) was decreased at 1.5 to 1.675 wt.% of MBA due to increase in ordered structure and crystallinity content, which led to an increase in Tm .